AN ANALYSIS OF COMPUTER-MEDIATED COMMUNICATION FOUND IN FACEBOOK STATUS - A, WULAN SUCI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Ariestawati,  Wulan  Suci. 2014.  An Analysis of Computer-Mediated Communication Found in Facebook Status.  Study Program of English, Universitas Brawijaya. Supervisor: Endang Sasanti; Co-Supervisor: Ida Puji Lestari  Keywords: Computer  –  Mediated Communication, Oral and written language, facebook status.  Language is a major element in a human society, especially for communication. There are two forms of how a language is produced, namely oral (spoken) and written forms. Computer-Mediated Communication (CMC) is a kind of communication  by computer  today which have both oral and written forms. Facebook is a popular social networking sites which can be included into one of CMC  types. The writer conducted a research about language phenomenon  found in facebook status to see how the written theory has changed with the coming of CMC. There are two problems to be solved the study, those are : (1) What the characteristics of Computer-Mediated Communication which are used by facebook users, and (2) What the factors influencing facebook status which have the characteristics of Computer-Mediated Communication.  This study uses the Paolillo’s theory (2001) about characteristics of CMC.  Those  are  orthography, vocabulary, grammar, discourse text, and paralinguistic graphic. This study uses qualitative approach especially document or textual analysis because it analyzes the sentences in facebook status. The researcher has 103 facebook status which have characteristics of CMC. The characteristics found in facebook status are orthography, vocabulary, grammar, discourse text, and paralinguistic graphic. Sometimes,  a facebook status has more than a characteristic of CMC. But, the characteristic mostly found in facebook status is paralinguistic graphic with the total of  92  status, followed by 45 status of grammar characteristic. The next one is 36 status of orthography, followed by discourse text with the total of 19 status. The last characteristic is vocabulary. It has 17 status.  From 103 facebook status,  there is just  one  status which  has not characteristic of CMC and it is  standard of written language. Actually, there are some factors  why people use the characteristics  of CMC, but in this research, there are gender and age factors which can be clearly seen in  facebook. As the conclusion, characteristics of CMC really exist in the social media, especially in facebook status. People are free to write everything they want in social media without thinking about the formality or standardization of the language. The researcher suggests to the next researchers to find out other language phenomena because those are interesting topic for the readers. For the example is Bahasa alay  phenomenon. It is confusing for some people. They can ask the participants about the meaning of the sentences in Bahasa alay. She also suggests to discuss other social media, like twitter, blog, blackberry messenger, and so on. In addition, it is also expected that the next researchers  use more  various approaches to analyze the data.